PERAN GURU MENGASAH POLA PIKIR KRITIS MELALUI METODE DISKUSI DAN TANYA JAWAB SISWA KELAS 3A DI SDN 08 MAMBORO - Wahyu Cahyani; Redna (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to explain the importance of the teacher's role in developing students' critical thinking skills through the discussion and question-and-answer method. The main subjects of this study were 19 third-grade students of class IIIA at SDN 08 Mamboro. This Classroom Action Research adopted the John Elliott model, where each cycle consisted of four main activities: planning, implementation, observation, and reflection, conducted over two cycles. Data collection techniques involved observation and interviews, while data analysis was carried out using a descriptive qualitative-quantitative approach. Quantitative analysis was used to determine the improvement in results through percentages. The findings showed that in the first cycle, student participation was still low (31.58%) due to a lack of understanding of the material and low self-confidence. A significant improvement in the second cycle (73.68%) demonstrated that guided discussions and structured question-and-answer sessions are effective in enhancing critical thinking skills. This proves that fostering critical thinking skills in students can prepare them to face higher-order thinking challenges and is relevant for implementation across various learning contexts.